Topological and Reactivity Descriptor of Carisoprodol from DFT and Molecular Docking Approach - Chaudhary, Tarun; Chaudhary, Manoj Kumar; Joshi, Bhawani Datt (Journal of Institute of Science and Technology, 2021)
This study aims to investigate the optimized structure and optimized parameters of carisoprodol from the DFT/B3LYP/6-31G(d,p) level of theory. The molecular electrostatic potential (MEP) map signifies that the positive potential across hydrogen of the amine group (NH2) and the negative potential around the carbonyl groups (C=O). HOMO-LUMO energy gap was found to be 8.1064 eV. The global and local reactivity parameters describe the possible chemical reactive sites in the molecule. The topological analysis of the electron localization function (ELF) and localized orbital locator (LOL) revealed that the charge localization around hydrogen atoms. The hyper-conjugative interaction between donor and acceptor orbital showed that the interaction LP(2) O4→ σ*(O2-C16) plays a vital role in the molecular stability. The molecular docking simulation encircles that the carisoprodol behaves as a good inhibitor with the target protein, Tyrosine-protein kinase ABL.